lncRNA MALAT-1 Predicts Prognosis of Patients with Systemic Lupus Erythematosus - Zhou, Aihong; Mao, Kunyun; Liu, Guoqiang; Li, Jun; Lin, Xia (Aktuelle Rheumatologie, 2021)
Objective To evaluate the association of MALAT-1 and the prognosis of patients with systemic lupus erythematosus (SLE).Materials and Methods A total of 87 SLE patients and 50 healthy controls were recruited. The expression levels of MALAT-1 were measured by quantitative PCR at baseline. Multivariate Cox regression analysis was performed to assess the association of MALAT-1 levels with survival after adjusting for potential confounding factors.Results The MALAT-1 levels in patients with SLE were significantly higher compared with healthy controls (p<0.01). The 10-year survival of patients with a higher MALAT-1 level was significantly lower than that of patients with a lower MALAT-1 level (HR=5.54; 95% CI: 1.49–20.55; p=0.01). Multivariate Cox regression indicated that the MALAT-1 level was significantly associated with a risk of mortality (HR=10.02, 95% CI: 1.14–88.14, p=0.04).Conclusion The expression levels of MALAT-1 may be a promising biomarker for evaluating the prognosis of SLE patients.
Keywords: MALAT-1; lncRNA; systemic lupus erythematosus; overall survival